Partisipasi Masyarakat Desa Lawang Agung Dalam Program Senam Sehat Setiap Hari Jumat - Riswati, Riga; Ulfah, Lendra; Muryaningsih, Azizah; Oktariani, Hesty; Anggraini, Kirana Widya; Artandi, Muhammad; Aditya, Muhammad; Kirana, Indira (Pakis Journal Institute, 2024)
This athletic endeavor has two goals: the first is to improve the body's resistance or immunity, and the second is to build the social relationships that exist amongst the people who live in Lawang Agung Village. The ABCD technique is the methodology that was used in this research. This method entails the creation of sporting activities and the active engagement of inhabitants of Lawang Agung Village, which is situated in Seluma Regency, Bengkulu. In order to ensure that the event was a success, the execution of this activity was carried out at the Lawang Agung Village Office, which is situated in the Seluma Regency of Bengkulu. This activity had a beneficial effect, as seen by the elevated level of excitement displayed by the community. The information provided by this service suggests that there are still a significant number of individuals who have never engaged in any kind of morning exercise. This is the primary reason for organizing sporting activities, particularly for the residents of Lawang Agung Village, which is situated in the Seluma Regency of Bengkulu. We believe that by participating in this activity, we will be able to inspire a greater number of people to take part in sporting activities that will help them maintain their health and improve their fitness levels. It is anticipated that the whole community of Lawang Agung Village, which is situated in Seluma Regency, Bengkulu, would be made aware of the significance of morning exercise as a component of a healthy lifestyle. This is done in order to ensure that it may bring about positive advantages to the welfare and health of all individuals from the community.